Exploring the driving factors of bird diversity in mangrove natural protected areas in Guangdong Province, China - Yang, Xitao; Wen, Rushu; Zhang, ChunXia; Qu, Ming; Luo, Jianing; Yu, Ruijuan; Zhao, Yan; Hua, Guodong; Tan, Kaiyuan; Yu, Lu; Ye, Sijia (Frontiers in Ecology and Evolution, 2024)
IntroductionUnder the impacts of high intensity human activities, mangrove natural protected areas are pivotal strategies for biodiversity conservation and play a significant role in preserving bird diversity. Mangrove natural protected areas in Guangdong Province, China, lie along the migratory path of the East Asian-Australasian Flyway, serving as breeding, feeding, and resting grounds for birds. Variations in bird responses to environmental factors are significant.MethodsTo comprehensively understand these variances, redundancy analysis was employed, focusing on bird diversity surveys conducted from March 2022 to February 2023 in natural protected areas of Guangdong to examine how driving factors such as mangrove habitat landscape, community structure, water quality, and soil sedimentation affected the diversity of avian species.ResultsThe findings were as follows: (1) A total of 193 bird species spanning 17 orders and 53 families were documented, including 74 songbirds, 60 wading birds, 27 swimming birds, 17 climbing birds, 10 raptors, and 5 terrestrial birds. (2) Regarding the impact of simple effects on all bird species, aquaculture pond area, mangrove extent, and mudflat area emerged as significant factors driving bird diversity, with explanatory rates of 31.0%, 28.9%, and 20.3%, respectively. Notably, the aquaculture pond area was the main driver of bird diversity, with an explanatory rate of 31.0%. (3) Mangrove extent has emerged as a pivotal factor shaping the songbird diversity, climbing birds, raptors, and terrestrial birds, whereas the aquaculture pond area was pivotal for wading birds, swimming birds, and others.DiscussionTo enhance mangrove bird diversity protection, management agencies overseeing natural mangrove protected areas should adopt science-based approaches when managing mangrove, mudflats, and aquaculture pond areas in mangrove forest protection and restoration plans. This would prevent extensive mangrove planting, which encroaches on non-mangrove habitats. Additionally, the scientific management of aquaculture ponds should accommodate diverse bird habitats through measures, such as water level adjustments.